Thermochemistry of formation of iron and antimony alloys: experiment and modeling - Усенко, Н.; Котова, Н.; Іванов, М.; Головата, Н. (Київський національний університет імені Тараса Шевченка, 2015)
The thermochemical properties of binary liquid Fe-Sb alloys were determined by high temperature isoperibolic calorimetry. The determination of the partial enthalpies of mixing was carried out at 1723-1820 K in purified helium medium. It is shown that the process of alloying formation is accompanied by slight heat effects. The minimum value of the integral enthalpy of mixing () in the FeSb system is evaluated to be (–2.30.2) kJ·mol-1 at mole fraction of antimony equal to 0.5. The values of partial enthalpies for components at infinite dilution are equal to (8.20.9) kJ·mol-1 for iron and (7.21.0) kJ·mol-1 for antimony. These facts indicate a weak chemical interaction between the components of investigated alloys of iron with antimony due to the great size difference of the components. It is found that estimations of thermodynamic properties of liquid alloys based on the data for solid phases are not sufficiently reliable. Preference should be given to data obtained directly from the experiment. The simulation of mixing enthalpies of Fe-Sb melts is also performed using the model of "surrounded atom" and the associated ideal solution model. The complete applicability of these models to description of concentration dependences of the enthalpies of mixing for this system is shown. This fact allows wide use of these models for predictions of thermochemical properties of multicomponent systems which are difficult for direct experimental investigation.

Методом високотемпературної калориметрії в ізопериболічному режимі визначено термохімічні властивості рідких сплавів подвійної системи Fe-Sb. Дослідження парціальних ентальпій змішування виконано при 1723-1820 K у середовищі чистого гелію. Показано, що вивчені розплави цієї системи утворюються із незначним виділенням теплоти і характеризуються дуже малими екзотермічними теплотами змішування (=–2,30,2 кДж·моль-1 при мольній частці стибію 0,5), що свідчить про слабку хімічну взаємодію між компонентами у розплавах феруму із стибієм. Розраховано ентальпії змішування для всього концентраційного інтервалу за моделлю "оточеного атому" та теорією ідеального асоційованого розчину (МІАР). Показано, що застосування і моделі "оточеного атома", і моделі ідеального асоційованого розчину для металічних систем аналогічного типу є досить успішним. Цей факт надає можливість широкого використання їх для прогнозування термохімічних властивостей складних в експериментальному відношенні об'єктів.
Термохімія сплавоутворення феруму із стибієм: експеримент та моделювання
Keywords: iron; antimony; high temperature calorimetry; enthalpy of mixing; model of "surrounded atom"; ideal associated solution model; -; ферум; стибій; високотемпературна калориметрія; ентальпії змішування; модель "оточеного атому"; теорія ідеального асоційованого розчину; -